Development of anti‐HIV peptides based on a viral capsid protein. Issue 1 (January 2017) - Mizuguchi, Takaaki; Ohashi, Nami; Matsumoto, Daichi; Hashimoto, Chie; Nomura, Wataru; Yamamoto, Naoki; Murakami, Tsutomu; Tamamura, Hirokazu
Abstract: Peptide inhibitors with cell permeability targeting an HIV‐1 capsid (CA) protein might make therapeutic by regulating HIV‐1 replication. Overlapping fragment peptide libraries covering the whole sequence of an HIV‐1 CA protein have been synthesized with the addition of an octa‐arginyl moiety to increase their cell permeability. Amongst these peptides, several compounds which inhibit the HIV‐1 replication cycle have been found. Conjugation of cell‐penetrating functions such as an octa‐arginyl group to individual peptides in combination with the addition of chloroquine in cell‐based anti‐HIV assays was previously proven to be a useful assay method with which to search for active peptides. Anti‐HIV assays have been performed in the presence or absence of chloroquine and found that most of compounds have higher anti‐HIV activity in the presence, rather than in the absence of chloroquine. Some potent seeds as anti‐HIV agents might naturally lie hidden in CA proteins, and could become useful leads to HIV inhibitors.